Les TICE et les arts comme outils de revitalisation des langues minorisées ? - Charlène Chaupré-Berki (Lengas)
This article focuses on the linguistic dynamics in the Roya Valley and Western Liguria, exploring local languages and assessing their vitality. The study is based on sociolinguistic surveys and interviews to understand the linguistic realities from the point of view of the speakers. CTBTs and audiovisual arts are emerging as promising mediation tools in the face of the challenges of linguistic discrimination, the lack of intergenerational transmission and the threat of the disappearance of minority languages. ICT and arts-based initiatives are suggested to promote and safeguard local languages, thereby strengthening community engagement. The emical perspective enriches the understanding of linguistic preservation, consolidating cultural identity and contributing to the preservation of linguistic diversity in a context of constant evolution.